Synchronization of estrus and insemination time in beef cows - M.D. Heekin; G.H. Kiracofe; R.R. Schalles; H.S. Ward (Kansas Agricultural Experiment Station Research Reports, 1977)
We used 76 cows to determine the effect of inseminating at different times after detecting estrus and to evaluate Synchronization B as an estrus synchronizing agent. Cows were divided into five groups: (1) nonsynchronized bred naturally; (2) nonsynchronized bred once a day approximately 12 to 24 hours after detecting estrus; (3) nonsynchronized bred twice a day approximately 12 hours after estrus; (4) synchronized bred once a day, and (5) synchronized bred twice a day. Synchronizing did not affect conception rate with twice-a-day breeding, but did with once-a-day breeding. Conception rates during the first 25 days of the breeding season were 63.6, 70.0, 69.2, 40.0, 80.0 for groups 1 through 5, respectively.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Synchronization; Estrus; Conception rates